2016
DOI: 10.1590/0004-282x20160030
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Brazilian version of the neurological fatigue index for multiple sclerosis

Abstract: Fatigue is the most frequent and severe of symptoms causing morbidity and disability in multiple sclerosis (MS) patients. However, measuring fatigue is a difficult task. There is no clear definition; it is complex and multidimensional, and is a highly subjective symptom with many uncertainties regarding its pathophysiology. No biological or neuroimaging markers for fatigue are currently known 1 . The lack of standardization for fatigue measurement has resulted in development of several assessment instruments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Consistent with previous studies, 42,43 there were no ceiling or floor effects in the C-NFI-Stroke. This study indicated that differences in fatigue could be discerned among participants and clinically meaningful data could be captured at two ends of the scale.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, 42,43 there were no ceiling or floor effects in the C-NFI-Stroke. This study indicated that differences in fatigue could be discerned among participants and clinically meaningful data could be captured at two ends of the scale.…”
Section: Discussionsupporting
confidence: 91%
“…The C-NFI-Stroke had smaller measurement errors than other neurological fatigue indices (e.g. 8.3%-9.2% for the Dutch Neurological Fatigue Index-multiple sclerosis; 41 5.4%-20.8% for the Brazilian Neurological Fatigue Index-multiple sclerosis; 42 and 4.8%-8.1% for the Neurological Fatigue Index-Post-Polio Syndrome). 43 Our findings support the argument that the C-NFI-Stroke is a reliable instrument for use in Chinese stroke populations.…”
Section: Discussionmentioning
confidence: 87%